PERMAINAN LARI KELERENG : PEMBENTUKKAN MOTORIK KASAR ANAK USIA DINI - Rabitah Hanum Hasibuan Veryawan veryawan; Rabitah Hanum Hasibuan (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2022)
The problem in this study is the low gross motor skills in using large muscles such as walking, running, jumping. This study aims to determine the effect of marbles running game activities on gross motor skills of children aged 5-6 years. This research was conducted at RA Al-Hidayah which is located at Jalan Perintis Kemerdekaan No.76 Binjai Timur, Binjai City. This type of research is quantitative with an experimental method using a post-test only control group design using non-parametric statistics. Data collection techniques using observation. The results showed that with different treatments, the score for the gross motor skills of the experimental class children was 10.8, while the score obtained in the control class was 7.8. The conclusion shows that the value of = 0.025, n1 = 15, n2 = 15 so that the results are Zcount = -3.3 and Ztable = 1.96 with a Zcount> Ztable, then there is a significant difference between the gross motor skills of children aged 5-6 years. using the marbles running game and the control class using the sack running game.